Applying the Multi Theory Model (MTM) of health behavior change for explaining fruits and vegetables consumption behavior among African American women in Mississippi, USA - LaVonne Brown; Vinayak K. Nahar; Manoj Sharma (Journal of Health and Social Sciences)
Objective: The aim of this study was to explain fruit and vegetable consumption behavior through application of the multi-theory model (MTM) of health behavior change among African American women in Mississippi, USA. Methods: This study utilized a cross sectional design. A 39-item face and content valid questionnaire based on MTM was completed by participants drawn from churches. The study utilized a convenience quota sampling. Participants who reported that they consumed more than five cups of fruits and vegetables within the last 24 hours were excluded from the study. Stepwise multiple regressions were conducted to explain fruit and vegetable consumption behavior. Results: A total of 116 participants (66.5% response rate) completed the surveys. The mean age of participants was 48.8 years (SD 17.82, range 21 to 84). Modeling utilizing multiple regression showed that the MTM constructs of participatory dialogue (P = 0.009), behavioral confidence (P = 0.0001), and changes in the physical environment (P = 0.0001) accounted for 50.8% of the predictability in the intention to initiate fruit and vegetable consumption behavior. Further, 59.9% of the variance in sustenance of fruit and vegetable consumption behavior was explained by the constructs of practice for change (P = 0.016), emotional transformation (P = 0.0001), and changes in the social environment (P = 0.0001). Discussion and Conclusion: The study provides credible support to reify MTM framework for developing programs to increase fruit and vegetable consumption among African American women.